2004
DOI: 10.1111/j.1440-1630.2004.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in activities of daily living ability

Abstract: The objective of this study was to examine the relation between activities of daily living (ADL) ability and age among well people between three and 93 years of age. The study is one of descriptive comparison in design. Existing data from the international Assessment of Motor and Process Skills (AMPS) database were examined. The participants constituted a sample of 4398 persons who met the inclusionary criteria. All participants were evaluated using the Assessment of Motor and Process Skills (AMPS). The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 13 publications
3
39
0
1
Order By: Relevance
“…Numerous studies support the reliability of the AMPS ability measures (23,24), as well as validity across age groups and genders (25,26). The AMPS has also been shown to be a sensitive outcome measure (27,28).…”
Section: Instrumentationmentioning
confidence: 96%
“…Numerous studies support the reliability of the AMPS ability measures (23,24), as well as validity across age groups and genders (25,26). The AMPS has also been shown to be a sensitive outcome measure (27,28).…”
Section: Instrumentationmentioning
confidence: 96%
“…Although the findings of the current study were not significant, it is suggested that future studies investigating alternative ways to improve response times should consider the effect of reduced attention (i.e., performance of concurrent tasks) on RT skills. It is thus presumed that by doing so, greater transfer effects can take place to improve driving and provide older people further independence and social contact with the wider community (Hayase et al, 2004). …”
Section: Discussionmentioning
confidence: 98%
“…The measurement model also makes adjustments to account simultaneously for skill item difficulty, rater severity, task difficulty, and participant ability. 20,21 The AMPS has been standardized on 4482 children aged 3 to 15 years worldwide, 22 with normative means calculated for the age groups 3 to 8 years and 9 to 15 years. 4 Established cut-offs for performance on the AMPS are two logits for ADL motor ability and one logit for ADL process ability.…”
Section: Methodsmentioning
confidence: 99%